A New Understanding of the Poyang Lake‐Yangtze River Interaction: A Backwater Effect on the Yangtze River Perspective - Yuanyuan Meng; Liguang Jiang; Erhu Du; Xingxing Zhang; Weijie Wang; Lei Wang (Geophysical Research Letters)
Abstract Interconnected river‐lake systems are much more complex than either one due to their interactions. The Poyang Lake‐Yangtze River system has received much attention due to the reverse flow from the Yangtze River, which blocks the flow of Poyang Lake and causes extensive inundation. However, a less explored perspective is the backwater effects of lake outflow on the Yangtze River. This study seeks to fill this gap by investigating the water surface slope (WSS) along the 294 km reach upstream of the confluence. Results show that huge variations of WSS (the maximum doubles the minimum) occur due to the dynamics of lake outflow and river discharge. The backwater can extend upstream to around 74 km. Elevated water level at Jiujiang can be up to 14.1 m in the worst case. The findings can advance our understanding of complex hydrodynamic processes in river‐lake systems and provide important policy implications for flood management.